Anti-fouling ceramic glaze water, anti-fouling ceramic and preparation method of anti-fouling ceramic
By using specific ratios of anti-fouling ceramic glaze water in ceramic products, including quartz, calcite, doped silicon nitride connecting agent and modification regulator, the problems of soil resistance, wear resistance and frost resistance of ceramic products are solved. , significantly improves the performance stability of ceramic products.
Patent Information
- Application Number
- CN202411854789.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The stain resistance, wear resistance and mechanical strength of existing ceramic products are difficult to balance, and the frost resistance and corrosion resistance are poor, which limits the efficiency of the product.
Using a stain-resistant ceramic glaze water, including quartz, calcite, silicon nitride doped connecting agent, zinc oxide and modification regulator, the active performance of silicon nitride is stimulated by proton irradiation, and through sodium silicate solution and Sodium dodecylbenzenesulfonate is blended with nanomica powder, boron oxide and basalt fibers to continuously mix sodium alginate agent to coordinate the blending between raw materials to form efficient ceramic glaze water, glazed and sintered.
It significantly improves the mechanical strength, soil resistance and wear resistance of ceramic products, while improving the freezing resistance and corrosion resistance stability, achieving coordinated and balanced performance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to an anti-fouling ceramic glaze, an anti-fouling ceramic and a preparation method thereof. Background Art
[0002] Ceramics is a general term for pottery and porcelain. Common ceramic materials include clay, alumina, kaolin, etc. Ceramic materials are generally hard but less plastic. In addition to being used in tableware and decoration, ceramics also play an important role in the development of science and technology. Ceramic raw materials are made from clay, a large amount of resources originally available on the earth, through quenching.
[0003] Existing ceramic products are glazed with anti-fouling glaze water, and the products have poor anti-fouling performance and wear resistance. It is difficult to improve the mechanical strength, anti-fouling and wear resistance of the products in a balanced manner. At the same time, the products have poor frost resistance and corrosion resistance stability, which further limits the product's use efficiency. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide an anti-fouling ceramic glaze, an anti-fouling ceramic and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides an anti-fouling ceramic glaze, comprising the following raw materials in parts by weight: 10-15 parts of quartz, 5-10 parts of calcite, 5-8 parts of a bonding agent doped with silicon nitride, 4-7 parts of zinc oxide, 4-7 parts of spodumene, and 4-7 parts of a modifying regulator.
[0006] Preferably, the preparation method of the silicon nitride doped bonding agent is: S01: placing silicon nitride in a proton irradiation box for irradiation treatment, the irradiation power is 350-400W, the irradiation is for 5-10 minutes, and the irradiation is completed to obtain irradiated silicon nitride; The irradiated silicon nitride, sodium silicate solution and sodium dodecylbenzene sulfonate are mixed thoroughly in a weight ratio of 2:5:1 to obtain a silicon nitride doping solution; S02: Preparation of the linking agent: S021: First immerse the boron oxide in a 5% yttrium nitrate solution with a mass fraction of 3-5 times the total weight of the boron oxide to obtain a boron oxide agent; S022: Add 2-5 parts of boron oxide and 2-3 parts of nano-mica powder to 2-5 parts of sodium citrate solution by weight, and then add 1-2 parts of silane coupling agent to mix and stir. After stirring, filter and dry to obtain a linking agent; S03: The silicon nitride doping liquid and the connecting agent are mixed in a weight ratio of 5:3, and the ball milling is performed at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a connecting agent doped with silicon nitride.
[0007] Preferably, the mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the sodium citrate solution is 4-7%; and the silane coupling agent is silane coupling agent KH560.
[0008] Preferably, the ultrasonic power for full immersion in S021 is 550-750W, and the ultrasonic immersion time is 1-2h; The stirring speed of the blending and stirring treatment in S022 is 400-500 r / min, and the stirring time is 30-40 min.
[0009] Preferably, the preparation method of the modified regulator is: S101: adding 2-4 parts of nano-silica and 1-3 parts of nano-silica sol to 5-8 parts of sodium lignin sulfonate solution by weight and mixing them evenly, and then adding 2-4 parts of chitosan solution and continuing to mix well to obtain nano-silica liquid; S102: Mix the nano-silica liquid, basalt fiber and sodium alginate agent in a weight ratio of 5:3 and perform ball milling at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, wash with water, filter and dry to obtain a modified regulator.
[0010] Preferably, the mass fraction of the sodium lignin sulfonate solution is 2-5%; the mass fraction of the chitosan solution is 3-6%.
[0011] Preferably, the preparation method of basalt fiber continuous sodium alginate agent is: The basalt fiber is first preheated at 55-60°C for 10-15 minutes, and then 5-8 parts of the preheated basalt fiber, 2-4 parts of 4-6% by mass lanthanum chloride solution and 5-8 parts of 5% by mass sodium alginate solution are blended and ball-milled by weight at a ball-milling speed of 1000r / min for 2h. After the ball-milling is completed, the mixture is filtered and dried to obtain the basalt fiber continuous sodium alginate agent.
[0012] The present invention provides a method for preparing anti-fouling ceramic glaze, comprising the following steps: All raw materials of anti-fouling ceramic glaze are fully wet-milled at a ball milling speed of 1500r / min for 2h, and anti-fouling ceramic glaze is obtained after the ball milling is completed.
[0013] The present invention provides a method for preparing anti-fouling ceramics, using the anti-fouling ceramic glaze, comprising the following steps: Step 1: Mix 12-15 parts of calcined talc, 14-17 parts of potassium feldspar, 15-18 parts of kaolin, 13-15 parts of mullite and 35-40 parts of water by weight, add them into a ball mill for wet ball milling, the ball milling speed is 1000r / min, the ball milling is performed for 1h, and the ball milling is completed to obtain a ball mill material; Step 2: re-shape the ball mill material at a shaping pressure of 5-10 MPa for 20 minutes to obtain a ceramic body; Step 3: applying anti-fouling ceramic glaze water to the surface of the ceramic body, and completing the glazing to obtain an anti-fouling ceramic body; Step 4: The anti-fouling ceramic body is finally sintered, and after the sintering is completed, the anti-fouling ceramic is obtained.
[0014] Preferably, the glaze amount of the anti-fouling ceramic glaze is 500-550g / m 2 ; The specific operation steps of sintering treatment are: First, heat to 550℃ at a rate of 2-5℃ / min, keep warm for 1-2h, then heat to 1250-1270℃ at a rate of 1-3℃ / min, keep warm for 2-5h, and finally air cool to room temperature.
[0015] The invention provides an anti-fouling ceramic, which is prepared by the preparation method of the anti-fouling ceramic.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The anti-fouling ceramic of the present invention is processed by ball milling of burnt talc, potassium feldspar, kaolin, mullite and water, improved by wet ball milling, and formed into a ceramic body by blending and coordinating the raw materials, and glazed with anti-fouling ceramic glaze water, and then sintered to obtain a ceramic product. The anti-fouling ceramic glaze water is blended with quartz, calcite, zinc oxide and spodumene, and then a linking agent and a modifying regulator doped with silicon nitride are added, and the two are coordinated and synergistic, so that the mechanical strength, anti-fouling and wear resistance of the obtained product are improved, and the antifreeze and corrosion resistance stability of the product are remarkable; 2. The silicon nitride doped linking agent uses silicon nitride to stimulate its active efficiency through proton irradiation, and then obtains a silicon nitride doped liquid by blending and coordinating with sodium silicate solution and sodium dodecylbenzene sulfonate. Boron oxide is treated with yttrium nitrate solution, and nano-mica powder, sodium citrate solution and silane coupling agent are mixed and stirred. Through the coordination between the raw materials, nano-mica powder is coordinated with boron oxide agent to synergistically improve the silicon nitride doped liquid, so that the performance of the obtained product can be coordinated and balanced, and the product's antifreeze and corrosion resistance stability are significantly improved; 3. The modified regulator adopts nano-silica and nano-silica sol, which are added to the sodium lignin sulfonate solution and mixed evenly, and then chitosan solution is added to continue mixing. Nano-silica is used to coordinate with chitosan solution and other raw materials. At the same time, the basalt fiber and sodium alginate agent are added to synergize with the nano-silica liquid to enhance the interfacial effect of the system. The basalt fiber and sodium alginate agent are blended and ball-milled by basalt fiber, lanthanum chloride solution and 5% sodium alginate solution by mass fraction. The basalt fiber is blended and coordinated with lanthanum chloride solution and sodium alginate solution to further enhance the synergistic effect of basalt fiber and sodium alginate with the nano-silica liquid, thereby further improving the performance of the product. DETAILED DESCRIPTION
[0017] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] An anti-fouling ceramic glaze of this embodiment includes the following raw materials in parts by weight: 10-15 parts of quartz, 5-10 parts of calcite, 5-8 parts of a bonding agent doped with silicon nitride, 4-7 parts of zinc oxide, 4-7 parts of spodumene, and 4-7 parts of a modifying regulator.
[0019] The preparation method of the silicon nitride doped bonding agent of this embodiment is as follows: S01: placing silicon nitride in a proton irradiation box for irradiation treatment, the irradiation power is 350-400W, the irradiation is for 5-10 minutes, and the irradiation is completed to obtain irradiated silicon nitride; The irradiated silicon nitride, sodium silicate solution and sodium dodecylbenzene sulfonate are mixed thoroughly in a weight ratio of 2:5:1 to obtain a silicon nitride doping solution; S02: Preparation of the linking agent: S021: First immerse the boron oxide in a 5% yttrium nitrate solution with a mass fraction of 3-5 times the total weight of the boron oxide to obtain a boron oxide agent; S022: Add 2-5 parts of boron oxide and 2-3 parts of nano-mica powder to 2-5 parts of sodium citrate solution by weight, and then add 1-2 parts of silane coupling agent to mix and stir. After stirring, filter and dry to obtain a linking agent; S03: The silicon nitride doping liquid and the connecting agent are mixed in a weight ratio of 5:3, and the ball milling is performed at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a connecting agent doped with silicon nitride.
[0020] The mass fraction of the sodium silicate solution in this embodiment is 2-5%; the mass fraction of the sodium citrate solution is 4-7%; and the silane coupling agent is silane coupling agent KH560.
[0021] The ultrasonic power for full immersion in S021 of this embodiment is 550-750W, and the ultrasonic immersion time is 1-2h; The stirring speed of the blending and stirring treatment in S022 is 400-500 r / min, and the stirring time is 30-40 min.
[0022] The preparation method of the modified regulator of this embodiment is: S101: adding 2-4 parts of nano-silica and 1-3 parts of nano-silica sol to 5-8 parts of sodium lignin sulfonate solution by weight and mixing them evenly, and then adding 2-4 parts of chitosan solution and continuing to mix well to obtain nano-silica liquid; S102: Mix the nano-silica liquid, basalt fiber and sodium alginate agent in a weight ratio of 5:3 and perform ball milling at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, wash with water, filter and dry to obtain a modified regulator.
[0023] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2-5%; the mass fraction of the chitosan solution is 3-6%.
[0024] The preparation method of the basalt fiber continuous sodium alginate agent of this embodiment is as follows: The basalt fiber is first preheated at 55-60°C for 10-15 minutes, and then 5-8 parts of the preheated basalt fiber, 2-4 parts of 4-6% by mass lanthanum chloride solution and 5-8 parts of 5% by mass sodium alginate solution are blended and ball-milled by weight at a ball-milling speed of 1000r / min for 2h. After the ball-milling is completed, the mixture is filtered and dried to obtain the basalt fiber continuous sodium alginate agent.
[0025] A method for preparing anti-fouling ceramic glaze comprises the following steps: All raw materials of anti-fouling ceramic glaze are fully wet-milled at a ball milling speed of 1500r / min for 2h, and anti-fouling ceramic glaze is obtained after the ball milling is completed.
[0026] A method for preparing anti-fouling ceramics, using the anti-fouling ceramic glaze, comprises the following steps: Step 1: Mix 12-15 parts of calcined talc, 14-17 parts of potassium feldspar, 15-18 parts of kaolin, 13-15 parts of mullite and 35-40 parts of water by weight, add them into a ball mill for wet ball milling, the ball milling speed is 1000r / min, the ball milling is performed for 1h, and the ball milling is completed to obtain a ball mill material; Step 2: re-shape the ball mill material at a shaping pressure of 5-10 MPa for 20 minutes to obtain a ceramic body; Step 3: applying anti-fouling ceramic glaze water to the surface of the ceramic body, and completing the glazing to obtain an anti-fouling ceramic body; Step 4: The anti-fouling ceramic body is finally sintered, and after the sintering is completed, the anti-fouling ceramic is obtained.
[0027] The glaze amount of the anti-fouling ceramic glaze in this embodiment is 500-550g / m 2 ; The specific operation steps of sintering treatment are: First, heat to 550℃ at a rate of 2-5℃ / min, keep warm for 1-2h, then heat to 1250-1270℃ at a rate of 1-3℃ / min, keep warm for 2-5h, and finally air cool to room temperature.
[0028] An anti-fouling ceramic is prepared by the preparation method of the anti-fouling ceramic.
[0029] Example 1: An anti-fouling ceramic glaze comprising the following raw materials in parts by weight: 10 parts of quartz, 5 parts of calcite, 5 parts of silicon nitride-doped bonding agent, 4 parts of zinc oxide, 4 parts of spodumene, and 4 parts of modified regulator.
[0030] The preparation method of the silicon nitride doped bonding agent of this embodiment is as follows: S01: placing silicon nitride in a proton irradiation box for irradiation treatment, the irradiation power is 350W, the irradiation is for 5 minutes, and the irradiation is completed to obtain irradiated silicon nitride; The irradiated silicon nitride, sodium silicate solution and sodium dodecylbenzene sulfonate are mixed thoroughly in a weight ratio of 2:5:1 to obtain a silicon nitride doping solution; S02: Preparation of the linking agent: S021: First immerse the boron oxide in a 5% yttrium nitrate solution with a mass fraction of 3 times the total weight of the boron oxide to obtain a boron oxide agent; S022: Add 2 parts of boron oxide and 2 parts of nano-mica powder to 2 parts of sodium citrate solution by weight, and then add 1 part of silane coupling agent to mix and stir. After stirring, filter and dry to obtain a linking agent; S03: The silicon nitride doping liquid and the connecting agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a connecting agent doped with silicon nitride.
[0031] The mass fraction of the sodium silicate solution in this embodiment is 2%; the mass fraction of the sodium citrate solution is 4-7%; and the silane coupling agent is silane coupling agent KH560.
[0032] In S021 of this embodiment, the ultrasonic power for full immersion is 550W, and the ultrasonic immersion time is 1h; The stirring speed of the blending and stirring treatment in S022 is 400 r / min, and the stirring time is 30 min.
[0033] The preparation method of the modified regulator of this embodiment is: S101: adding 2 parts of nano-silica and 1 part of nano-silica sol to 5 parts of sodium lignin sulfonate solution by weight and mixing them evenly, and then adding 2 parts of chitosan solution and continuing to mix well to obtain nano-silica liquid; S102: Mix the nano-silica liquid and the basalt fiber and sodium alginate agent in a weight ratio of 5:3 and perform ball milling at a ball milling speed of 1000 r / min for 1 hour. After the ball milling is completed, wash with water, filter and dry to obtain a modified regulator.
[0034] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2%; the mass fraction of the chitosan solution is 3%.
[0035] The preparation method of the basalt fiber continuous sodium alginate agent of this embodiment is as follows: The basalt fiber was preheated at 55°C for 10 min, and then 5 parts of the preheated basalt fiber, 2 parts of 4% by mass lanthanum chloride solution and 5 parts of 5% by mass sodium alginate solution were blended and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 h. After the ball-milling was completed, the mixture was filtered and dried to obtain the basalt fiber continuous sodium alginate agent.
[0036] A method for preparing anti-fouling ceramic glaze comprises the following steps: All raw materials of anti-fouling ceramic glaze are fully wet-milled at a ball milling speed of 1500r / min for 2h, and anti-fouling ceramic glaze is obtained after the ball milling is completed.
[0037] A method for preparing anti-fouling ceramics, using the anti-fouling ceramic glaze, comprises the following steps: Step 1: Mix 12 parts of calcined talc, 14 parts of potassium feldspar, 15 parts of kaolin, 13 parts of mullite and 35 parts of water by weight, add them into a ball mill for wet ball milling, the ball milling speed is 1000r / min, the ball milling is performed for 1h, and the ball milling is completed to obtain a ball mill material; Step 2: re-shape the ball mill material at a shaping pressure of 5 MPa for 20 minutes to obtain a ceramic body; Step 3: applying anti-fouling ceramic glaze water to the surface of the ceramic body, and completing the glazing to obtain an anti-fouling ceramic body; Step 4: The anti-fouling ceramic body is finally sintered, and after the sintering is completed, the anti-fouling ceramic is obtained.
[0038] The glaze amount of the anti-fouling ceramic glaze in this embodiment is 500g / m 2 ; The specific operation steps of sintering treatment are: First, heat to 550°C at a rate of 2°C / min, keep warm for 1 hour, then heat to 1250°C at a rate of 1°C / min, keep warm for 2 hours, and finally air cool to room temperature.
[0039] An anti-fouling ceramic is prepared by the preparation method of the anti-fouling ceramic.
[0040] Example 2: A method for preparing anti-fouling ceramics using an anti-fouling ceramic glaze comprising the following raw materials in parts by weight: 15 parts of quartz, 10 parts of calcite, 8 parts of a linking agent doped with silicon nitride, 7 parts of zinc oxide, 7 parts of spodumene, and 7 parts of a modifying regulator.
[0041] The preparation method of the silicon nitride doped bonding agent of this embodiment is as follows: S01: placing silicon nitride in a proton irradiation box for irradiation treatment, the irradiation power is 400W, the irradiation is for 10 minutes, and the irradiation is completed to obtain irradiated silicon nitride; The irradiated silicon nitride, sodium silicate solution and sodium dodecylbenzene sulfonate are mixed thoroughly in a weight ratio of 2:5:1 to obtain a silicon nitride doping solution; S02: Preparation of the linking agent: S021: First immerse the boron oxide in a 5% yttrium nitrate solution with a mass fraction of 5 times the total weight of the boron oxide to obtain a boron oxide agent; S022: Add 5 parts of boron oxide and 3 parts of nano-mica powder to 5 parts of sodium citrate solution by weight, and then add 2 parts of silane coupling agent to mix and stir. After stirring, filter and dry to obtain a linking agent; S03: The silicon nitride doping liquid and the connecting agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a connecting agent doped with silicon nitride.
[0042] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the sodium citrate solution is 7%; and the silane coupling agent is silane coupling agent KH560.
[0043] In S021 of this embodiment, the ultrasonic power for full immersion is 750W, and the ultrasonic immersion time is 2h; The stirring speed of the blending and stirring treatment in S022 is 500 r / min, and the stirring time is 40 min.
[0044] The preparation method of the modified regulator of this embodiment is: S101: adding 4 parts of nano-silica and 3 parts of nano-silica sol to 8 parts of sodium lignin sulfonate solution by weight and mixing them evenly, and then adding 4 parts of chitosan solution and continuing to mix well to obtain nano-silica liquid; S102: Mix the nano-silica liquid and the basalt fiber and sodium alginate agent in a weight ratio of 5:3 and perform ball milling at a ball milling speed of 1500 r / min for 1 hour. After the ball milling is completed, wash with water, filter and dry to obtain a modified regulator.
[0045] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5%; the mass fraction of the chitosan solution is 6%.
[0046] The preparation method of the basalt fiber continuous sodium alginate agent of this embodiment is as follows: The basalt fiber was preheated at 60°C for 15 min, and then 8 parts of the preheated basalt fiber, 4 parts of 6% by mass lanthanum chloride solution and 8 parts of 5% by mass sodium alginate solution were blended and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 h. After the ball-milling was completed, the mixture was filtered and dried to obtain the basalt fiber continuous sodium alginate agent.
[0047] A method for preparing anti-fouling ceramic glaze comprises the following steps: All raw materials of anti-fouling ceramic glaze are fully wet-milled at a ball milling speed of 1500r / min for 2h, and anti-fouling ceramic glaze is obtained after the ball milling is completed.
[0048] A method for preparing anti-fouling ceramics, using the anti-fouling ceramic glaze, comprises the following steps: Step 1: Mix 15 parts of calcined talc, 17 parts of potassium feldspar, 18 parts of kaolin, 15 parts of mullite and 40 parts of water by weight, add them into a ball mill for wet ball milling, the ball milling speed is 1000r / min, the ball milling is performed for 1h, and the ball milling is completed to obtain a ball mill material; Step 2: re-shaping the ball mill material, with a shaping pressure of 10 MPa and shaping for 20 minutes to obtain a ceramic body; Step 3: applying anti-fouling ceramic glaze water to the surface of the ceramic body, and completing the glazing to obtain an anti-fouling ceramic body; Step 4: The anti-fouling ceramic body is finally sintered, and after the sintering is completed, the anti-fouling ceramic is obtained.
[0049] The glaze amount of the anti-fouling ceramic glaze in this embodiment is 550g / m 2 ; The specific operation steps of sintering treatment are: First, heat to 550°C at a rate of 5°C / min, keep warm for 2h, then heat to 1270°C at a rate of 3°C / min, keep warm for 5h, and finally air cool to room temperature.
[0050] An anti-fouling ceramic is prepared by the preparation method of the anti-fouling ceramic.
[0051] Example 3: An anti-fouling ceramic glaze comprising the following raw materials in parts by weight: 12.5 parts of quartz, 7.5 parts of calcite, 6.5 parts of silicon nitride-doped bonding agent, 5.5 parts of zinc oxide, 5.5 parts of spodumene, and 5.5 parts of modification regulator.
[0052] The preparation method of the silicon nitride doped bonding agent of this embodiment is as follows: S01: placing silicon nitride in a proton irradiation box for irradiation treatment, the irradiation power is 370W, the irradiation is for 7.5 minutes, and the irradiation is completed to obtain irradiated silicon nitride; The irradiated silicon nitride, sodium silicate solution and sodium dodecylbenzene sulfonate are mixed thoroughly in a weight ratio of 2:5:1 to obtain a silicon nitride doping solution; S02: Preparation of the linking agent: S021: First immerse the boron oxide in a 5% yttrium nitrate solution with a mass fraction of 4 times the total weight of the boron oxide to obtain a boron oxide agent; S022: Add 3.5 parts of boron oxide and 2.5 parts of nano-mica powder to 3.5 parts of sodium citrate solution by weight, and then add 1.5 parts of silane coupling agent to mix and stir. After stirring, filter and dry to obtain a linking agent; S03: The silicon nitride doping liquid and the connecting agent are mixed in a weight ratio of 5:3, and the ball milling is performed at a ball milling speed of 1250 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a connecting agent doped with silicon nitride.
[0053] The mass fraction of the sodium silicate solution in this embodiment is 3.5%; the mass fraction of the sodium citrate solution is 5.5%; and the silane coupling agent is silane coupling agent KH560.
[0054] In S021 of this embodiment, the ultrasonic power for full immersion is 600W, and the ultrasonic immersion time is 1.5h; The stirring speed of the blending and stirring treatment in S022 is 450 r / min, and the stirring time is 35 min.
[0055] The preparation method of the modified regulator of this embodiment is: S101: adding 3 parts of nano-silica and 2 parts of nano-silica sol to 6.5 parts of sodium lignin sulfonate solution by weight and mixing them evenly, and then adding 3 parts of chitosan solution and continuing to mix well to obtain nano-silica liquid; S102: Mix the nano-silica liquid and the basalt fiber and sodium alginate agent in a weight ratio of 5:3, and perform ball milling at a ball milling speed of 1250 r / min for 1 h. After the ball milling is completed, wash with water, filter, and dry to obtain a modified regulator.
[0056] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 3.5%; the mass fraction of the chitosan solution is 4.5%.
[0057] The preparation method of the basalt fiber continuous sodium alginate agent of this embodiment is as follows: The basalt fiber was preheated at 57°C for 12.5 min, and then 6.5 parts of the preheated basalt fiber, 3 parts of 5% by mass lanthanum chloride solution and 6.5 parts of 5% by mass sodium alginate solution were blended and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 h. After the ball-milling was completed, the mixture was filtered and dried to obtain the basalt fiber continuous sodium alginate agent.
[0058] A method for preparing anti-fouling ceramic glaze comprises the following steps: All raw materials of anti-fouling ceramic glaze are fully wet-milled at a ball milling speed of 1500r / min for 2h, and anti-fouling ceramic glaze is obtained after the ball milling is completed.
[0059] A method for preparing anti-fouling ceramics, using the anti-fouling ceramic glaze, comprises the following steps: Step 1: 13.5 parts of calcined talc, 15.5 parts of potassium feldspar, 16.5 parts of kaolin, 14 parts of mullite and 37.5 parts of water are mixed by weight and added into a ball mill for wet ball milling at a ball milling speed of 1000 r / min for 1 hour to obtain a ball milled material; Step 2: re-shaping the ball mill material, with a shaping pressure of 7.5 MPa and shaping for 20 minutes to obtain a ceramic body; Step 3: applying anti-fouling ceramic glaze water to the surface of the ceramic body, and completing the glazing to obtain an anti-fouling ceramic body; Step 4: The anti-fouling ceramic body is finally sintered, and after the sintering is completed, the anti-fouling ceramic is obtained.
[0060] The glaze amount of the anti-fouling ceramic glaze in this embodiment is 520g / m 2 ; The specific operation steps of sintering treatment are: First, heat to 550°C at a rate of 3.5°C / min, keep warm for 1.5h, then heat to 1260°C at a rate of 2°C / min, keep warm for 3.5h, and finally air cool to room temperature.
[0061] An anti-fouling ceramic is prepared by the preparation method of the anti-fouling ceramic.
[0062] Comparative Example 1: The difference from Example 3 is that no bonding agent doped with silicon nitride is added.
[0063] Comparative Example 2: The difference from Example 3 is that no silicon nitride doping liquid is added in the preparation of the silicon nitride doped bonding extender.
[0064] Comparative Example 3: The difference from Example 3 is that no linking agent treatment is used in the preparation of the linking agent doped with silicon nitride.
[0065] Comparative Example 4: The difference from Example 3 is that no boron oxide agent is added to the linking agent.
[0066] Comparative Example 5: The difference from Example 3 is that the boron oxide agent is replaced by boron oxide.
[0067] Comparative Example 6: The difference from Example 3 is that no nano-mica powder and silane coupling agent are added to the linking agent.
[0068] Comparative Example 7: The difference from Example 3 is that no modifying regulator is added.
[0069] Comparative Example 8: The difference from Example 3 is that no nano-silicon dioxide liquid is added to the modified regulator.
[0070] Comparative Example 9: The difference from Example 3 is that no chitosan solution and nano-silica sol are added to the nano-silica liquid.
[0071] Comparative Example 10: The difference from Example 3 is that no basalt fiber and sodium alginate agent are added to the modified regulator.
[0072] The products of Examples 1-3 and Comparative Examples 1-10 were subjected to conventional performance tests. The products were placed at -10°C for 48 hours and then placed in 2% hydrochloric acid for 24 hours. The above was one cycle. The cycle was repeated 10 times. The performance test results are shown in Table 1.
[0073] Table 1 Product performance test results of Examples 1-3 and Comparative Examples 1-10: It can be concluded from Examples 1-3 and Comparative Examples 1-10 that the product of Example 3 of the present invention has excellent anti-fouling grade, wear resistance and bending strength under normal conditions, and also has excellent performance stability under frost resistance and acid corrosion resistance conditions; The present invention does not add any of the linking agent doped with silicon nitride and the modifying regulator, and the performance of the product has a significant tendency to deteriorate. The two are coordinated and coordinated to achieve the most significant product performance effect. In the preparation of the silicon nitride doped linking agent, no silicon nitride doping liquid was added, no linking agent treatment was used in the preparation of the silicon nitride doped linking agent, no boron oxide agent was added to the linking agent, the boron oxide agent was replaced by boron oxide, and no nano mica powder and silane coupling agent were added to the linking agent. The performance of the product has a tendency to deteriorate. The silicon nitride doping liquid obtained by the specific boron oxide agent and linking agent treatment of the present invention has the most significant performance effect of the product. The use of other methods instead is not as obvious as the effect of the present invention. The performance of the product tends to deteriorate when the nano-silica liquid, chitosan solution and nano-silica sol are not added to the modified regulator, and the basalt fiber continuous sodium alginate agent is not added to the modified regulator. The performance effect of the product is most significant when the nano-silica liquid obtained by the method of the present invention is combined with the basalt fiber continuous sodium alginate agent. At the same time, the performance of the product deteriorates significantly when the basalt fiber continuous sodium alginate agent is not added. Based on the fact that basalt fiber combined with sodium alginate agent has a significant impact on the performance of the product, further research is needed.
[0074] Experimental Example 1: The only difference from Example 3 is that no preheated basalt fiber is added in the preparation of the basalt fiber-adjusted sodium alginate agent.
[0075] Experimental Example 2: The only difference from Example 3 is that no lanthanum chloride solution is added in the preparation of the basalt fiber continuous sodium alginate agent.
[0076] Experimental Example 3: The only difference from Example 3 is that no sodium alginate solution is added in the preparation of the basalt fiber continuous sodium alginate agent.
[0077] Experimental Example 4: The only difference from Example 3 is that the mass fraction of the lanthanum chloride solution is 3%, and the mass fraction of the sodium alginate solution is 6%.
[0078] The products of Experimental Examples 1-4 were subjected to conventional performance tests. At the same time, the products were placed at -10°C for 48 hours, and then placed in 2% hydrochloric acid for 24 hours. The above was one cycle. The cycle treatment was repeated 10 times. The performance test results are shown in Table 2.
[0079] Table 2 Product performance test results of Experimental Examples 1-4: It can be seen from Experimental Examples 1-4 that preheated basalt fiber is not added in the preparation of basalt fiber and sodium alginate agent. In the preparation of basalt fiber and sodium alginate agent, the performance of the product deteriorates most significantly. At the same time, the performance of the product tends to deteriorate when no lanthanum chloride solution and no sodium alginate solution are added. The performance of the product also tends to deteriorate when the mass fractions of lanthanum chloride solution and sodium alginate solution are different. Only when the specific raw materials and specific mass fractions of the present invention are used, the performance effect of the product is most significant. Other methods are not as obvious as the effect of the present invention.
[0080] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0081] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A stain-resistant ceramic glaze, characterized in that: It includes the following raw materials in parts by weight: 10-15 parts of quartz, 5-10 parts of calcite, 5-8 parts of a linking agent doped with silicon nitride, 4-7 parts of zinc oxide, 4-7 parts of spodumene, and 4-7 parts of a modifying regulator.
2. The anti-fouling ceramic glaze according to claim 1, characterized in that: The preparation method of the silicon nitride doped bonding agent is as follows: S01: placing silicon nitride in a proton irradiation box for irradiation treatment, the irradiation power is 350-400W, the irradiation is for 5-10 minutes, and the irradiation is completed to obtain irradiated silicon nitride; The irradiated silicon nitride, sodium silicate solution and sodium dodecylbenzene sulfonate are mixed thoroughly in a weight ratio of 2:5:1 to obtain a silicon nitride doping solution; S02: Preparation of the linking agent: S021: First immerse the boron oxide in a 5% yttrium nitrate solution with a mass fraction of 3-5 times the total weight of the boron oxide to obtain a boron oxide agent; S022: Add 2-5 parts of boron oxide and 2-3 parts of nano-mica powder to 2-5 parts of sodium citrate solution by weight, and then add 1-2 parts of silane coupling agent to mix and stir. After stirring, filter and dry to obtain a linking agent; S03: The silicon nitride doping liquid and the connecting agent are mixed in a weight ratio of 5:3, and the ball milling is performed at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, the mixture is washed with water and dried to obtain a connecting agent doped with silicon nitride.
3. The anti-fouling ceramic glaze according to claim 2, characterized in that: The mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the sodium citrate solution is 4-7%; and the silane coupling agent is silane coupling agent KH560.
4. The anti-fouling ceramic glaze according to claim 2, characterized in that: The ultrasonic power for full immersion in S021 is 550-750W, and the ultrasonic immersion time is 1-2h; The stirring speed of the blending and stirring treatment in S022 is 400-500 r / min, and the stirring time is 30-40 min.
5. The anti-fouling ceramic glaze according to claim 1, characterized in that: The preparation method of the modified regulator is: S101: adding 2-4 parts of nano-silica and 1-3 parts of nano-silica sol to 5-8 parts of sodium lignin sulfonate solution by weight and mixing them evenly, and then adding 2-4 parts of chitosan solution and continuing to mix well to obtain nano-silica liquid; S102: Mix the nano-silica liquid, basalt fiber and sodium alginate agent in a weight ratio of 5:3 and perform ball milling at a ball milling speed of 1000-1500 r / min for 1 hour. After the ball milling is completed, wash with water, filter and dry to obtain a modified regulator.
6. The anti-fouling ceramic glaze according to claim 5, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 2-5%; the mass fraction of the chitosan solution is 3-6%.
7. The anti-fouling ceramic glaze according to claim 5, characterized in that: The preparation method of the basalt fiber continuous sodium alginate agent is as follows: The basalt fiber is first preheated at 55-60°C for 10-15 minutes, and then 5-8 parts of the preheated basalt fiber, 2-4 parts of 4-6% by mass lanthanum chloride solution and 5-8 parts of 5% by mass sodium alginate solution are blended and ball-milled by weight at a ball-milling speed of 1000r / min for 2h. After the ball-milling is completed, the mixture is filtered and dried to obtain the basalt fiber continuous sodium alginate agent.
8. A method for preparing anti-fouling ceramics, using the anti-fouling ceramic glaze according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Mix 12-15 parts of calcined talc, 14-17 parts of potassium feldspar, 15-18 parts of kaolin, 13-15 parts of mullite and 35-40 parts of water by weight, add them into a ball mill for wet ball milling, the ball milling speed is 1000r / min, the ball milling is performed for 1h, and the ball milling is completed to obtain a ball mill material; Step 2: re-shape the ball mill material at a shaping pressure of 5-10 MPa for 20 minutes to obtain a ceramic body; Step 3: applying anti-fouling ceramic glaze water to the surface of the ceramic body, and completing the glazing to obtain an anti-fouling ceramic body; Step 4: The anti-fouling ceramic body is finally sintered, and after the sintering is completed, the anti-fouling ceramic is obtained.
9. The method for preparing anti-fouling ceramics according to claim 8, characterized in that: The glaze amount of the anti-fouling ceramic glaze is 500-550g / m 2 ; The specific operation steps of sintering treatment are: First, heat to 550℃ at a rate of 2-5℃ / min, keep warm for 1-2h, then heat to 1250-1270℃ at a rate of 1-3℃ / min, keep warm for 2-5h, and finally air cool to room temperature.
10. An anti-fouling ceramic prepared by the method for preparing the anti-fouling ceramic according to claim 8 or 9.
Citation Information
Patent Citations
Waterproof high-strength basalt fiber asphalt mixture and preparation method thereof
CN111847988A
Self-adhesive paint for transposed conductor and coating method of self-adhesive paint
CN117264498A
Acrylate emulsion and application thereof in preparation of waterproof paint
CN117964830A
Preparation process of high-heat-resistance ceramic with non-sticky glaze surface
CN118993543A
Underglaze blue glaze water, underglaze blue ceramic and preparation method of underglaze blue ceramic
CN119038954A
Cited By
Wear-resistant ceramic clay and preparation method thereof
CN119930271A
A wear-resistant ceramic clay and its preparation method
CN119930271B
Anti-falling ceramic material, preparation method and application of anti-falling ceramic material in ceramic ornament
CN120229959A
A drop-resistant ceramic material, preparation method and application in ceramic ornaments
CN120229959B
High-temperature-resistant domestic ceramic product and preparation method thereof
CN120247540A